Modelling and Simulation of Mho Type Distance Relay for High Voltage Transmission Line Protection Using MATLAB Software - Win Win Tun; Ohn Zin Lin; Han Su Yin (Department of Electrical Engineering ITS and FORTEI, 2019)
Transmission lines are an important part of a power system. Transmission lines have high power transmission capacity and they are prone to faults of larger magnitudes. Various faults occur in transmission lines. Therefore, protection relays are necessary to protect transmission lines. The purpose of protection system is to interrupt the faulty section from the healthy section because the fault currents may damage the electrical equipments. One of the protection relays is distance relay and it is mainly used in transmission line. Sometimes these relay are used for backup protection. Distance relays for determining the impedance need the voltage and current. Transmission lines are typically protected by distance protection relay. Distance relays are considered of high speed class and can provide transmission lines. Nowadays, numerical distance relays have been used instead of using electromechanical and static distance relays. The proposed model was verified under different tests such as single line to ground (L-G) fault, double line to ground (L-L-G) fault, line to line (L-L) fault and three phase (L-L-L) fault. SimPower System was used for modelling and simulation of distance relay, transmission lines and faults. The simulation results were obtained from MATLAB software shows the feasibility of analysis of transmission line protection with mho type distance relay for single line to ground fault, double line to ground fault, line to line fault and three phase fault at different location of transmission lines. The difficulties understanding on operation of distance relay can be cleared by using MATLAB/SIMULINK software.Keywords: distance relay, double line to ground (L-L-G), line to line fault (L-L), MATLAB/SIMULINK, single line to ground fault (L-G), three phase fault (L-L-L).